Tension Mechanism Dynamic Analysis - Michal Lukac; Frantisek Brumercik; Leszek Krzywonos; Pawel Drozdziel (Communications - Scientific letters of the University of Zilina, 2014)
The aim of the presented article is to show how to create a mathematical model of the tension mechanism working by a spring motion generation and contacting a rigid body at the end of the motion.